A Study on Preschool Teachers' Perceived Conflict with School Administrators, Colleagues and Parents - (:unkn) unknown (TURKISH EDUCATION ASSOC, 2012)
Conflict is perceived as a major problem in educational organizations. The purpose of this study is to determine the reasons underlying conflict and solution for conflict situation by preschool teachers. A group of female teachers who work in state preschools and preschool classrooms in elementary schools in Istanbul in the 2009-2010 academic year constitutes the participants of this research. Qualitative research design was employed to conduct this study. A structured interview form was used to explore the perceived conflict situations by preschool teachers. The data of the study was analyzed and reported based on tree categories which are called as teacher-school principals' conflicts, teacher-teacher conflicts and teacher-parent conflicts. The findings indicated that teachers have experienced conflict with parents, administrators and teachers who work together. In addition, compromising and avoidance strategies often used by teachers in conflict resolution has emerged.
Keywords: Preschool; kindergarten; conflict